A water pricing model for urban areas based on water accessibility. (1st February 2023) - Xu, Lili; Tu, Zhenfa; Yang, Jian; Zhang, Chenlei; Chen, Xiaoxu; Gu, Yinxue; Yu, Guangming
Abstract: Water resource, with properties of scarcity, is one of the vital resource endowments. Like land resources, the prices of these resource endowments should be correlated to their locations to follow fair and reasonable principles. The current water price systems are mainly policy-oriented fixed regimes. And the water use was charged according to the regional-average situation with scarce consideration of the fine-scale geographical water accessibility. With a combination of the water accessibility and the current water pricing regime, this paper first proposed a novel water pricing model, the Water Price at Grid-scale (WPG) model, to dynamically allocate water prices to fine grids for urban residents. The WPG model was examined in the case study of the Han River Basin in the Hubei province of China. The specific results were: (1) the P grid of Tier I is between 0.66 and 3.94 yuan/m³, the P grid of Tier II is between 0.57 and 5.44 yuan/m³, and the P grid of Tier III is between 0.47 and 6.94 yuan/m³ in the study area. (2) the grids with more water acquisition generally have lower water prices than others and vice versa . (3) the average water prices in tiers obtained by the WPG model are generally higher than that derived from the current water pricing system. The results proved that the proposed WPG model spatially allocates the three-tier water prices into grids of urban areas. The WPG framework can be adopted in any society by involving its water price regimes and adjusting the scale of grids and the pricing year. This study provided a new viewpoint of domestic water pricing involving fine-scale water accessibility. The WPG model has great potential to ease water shortage pressure in water-limited societies and can be utilized and loaded into the current smart-city network for efficient and fine-scale water resource management. Graphical abstract: Image 1 Highlights: The location attributes of water resources should be considered in water pricing. The WPG model was proposed to endow with the location attributes to water prices. The SHRD model and the current water pricing regime were combined in the WPG model. The fine-scale three-tier water prices were obtained using WPG model in case area. The dynamic WPG framework can be loaded into smart city networks in any society.